2014
DOI: 10.1074/jbc.m114.558494
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism of the Bicopper Enzyme Peptidylglycine α-Hydroxylating Monooxygenase

Abstract: Background: Peptidylglycine ␣-hydroxylating monooxygenase catalyzes the generation of C-terminal carboxamides of peptide hormones, neurotransmitters, and growth factors for biological activation. Results: We compare several possible reaction mechanisms by means of quantum mechanics/molecular mechanics calculations. Conclusion: Our results suggest that the most likely abstracting species is [CuOOH] 2ϩ . Significance: Our computational study proposes a new mechanism, which explains the experimental observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 61 publications
0
38
0
1
Order By: Relevance
“…The relationship between copper-ligation and E S or S S reactivity requires elucidation. An intriguing point for consideration of monocopper O 2 -chemistry is that a new computational study [71] suggests that the reactive species in PHM is a [Cu II -O 2 •− (H)] 2+ entity, i.e., with a protonated superoxide. HO 2 (aq) is a much stronger HAT reagent than is O 2 •− anion [64].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between copper-ligation and E S or S S reactivity requires elucidation. An intriguing point for consideration of monocopper O 2 -chemistry is that a new computational study [71] suggests that the reactive species in PHM is a [Cu II -O 2 •− (H)] 2+ entity, i.e., with a protonated superoxide. HO 2 (aq) is a much stronger HAT reagent than is O 2 •− anion [64].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…HO 2 (aq) is a much stronger HAT reagent than is O 2 •− anion [64]. Even with the Lewis acidic Cu(II) ion present and ligated, perhaps [Cu II -O 2 •− (H)] 2+ , as suggested [71], is required to effect HAT chemistry producing R• + Cu II -OOH plus release of that “extra” proton.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…the superoxide complex, [Cu–OO], and an axial isomer of a Cu(II)–oxyl species [22], [Cu–O], has been considered in computational studies, but no other quantitative studies exist. A comprehensive computational study was performed by Abad et al [27], but for another copper monooxygenase with a different active site. In studies of inorganic model systems, it has been suggested that a Cu(III)–hydroxy species could be responsible for the hydrogen-atom abstraction in the LPMOs [2830].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is reasonable given that inactivation is turnover-dependent and that the PHM-catalyzed hydroxylation reaction likely proceeds through a substrate-based radical 3942 . However, this proposed chemistry is inconsistent with our data and is thermodynamically challenging.…”
Section: Discussionmentioning
confidence: 86%
“…The formation of vinyl radical during the cinnamate-mediated inactivation of PHM is mechanistically relevant because this would require the formation of a PAM-based oxidant that is sufficiently strong to abstract a hydrogen atom from the α-carbon of cinnamate. If true, this may force a revision of the current models for PHM catalysis 3942 .…”
Section: Introductionmentioning
confidence: 99%